2013
DOI: 10.1108/17574321311321603
|View full text |Cite
|
Sign up to set email alerts
|

Leadership and organizational citizenship behavior (OCB) in the financial service sector

Abstract: Leadership and organizational citizenship behavior (OCB) in the financial service sector:The case of the UAE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
37
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 88 publications
8
37
1
4
Order By: Relevance
“…Thus, it was verified that, in this sample, the leadership style based on relations of exchange and rewards between leaders and subordinates (Bass, 1990) was only effective to predict the behaviors associated with the dissemination of a good organizational image in its external environment. These results are consistent with different earlier studies (Asgari et al,2008;Podsakoff et al, 2000;Suliman & Obaidly, 2013;Whittington et al, 2009) that also found the predictive power of transactional leadership on the OCB. Transactional leadership basically rests on rewarding appropriate behaviors and punishing counterproductive behaviors (Bass, 1999).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Thus, it was verified that, in this sample, the leadership style based on relations of exchange and rewards between leaders and subordinates (Bass, 1990) was only effective to predict the behaviors associated with the dissemination of a good organizational image in its external environment. These results are consistent with different earlier studies (Asgari et al,2008;Podsakoff et al, 2000;Suliman & Obaidly, 2013;Whittington et al, 2009) that also found the predictive power of transactional leadership on the OCB. Transactional leadership basically rests on rewarding appropriate behaviors and punishing counterproductive behaviors (Bass, 1999).…”
Section: Discussionsupporting
confidence: 93%
“…In that sense, different studies (Mackenzie, Podsakoff, & Rich, 2001;Omar et al, 2009;Zabihi & Hashemzehi, 2012) and meta-analyses (Wang et al, 2011) have evidenced the stronger power of the transformational leadership style to explain the OCB than the transactional leadership style. There is no consensus on these results though, as other studies have concluded that transactional leadership has greater predictive power on the OCB when compared to transformational leadership (Suliman & Obaidly, 2013;Whittington et al, 2009). Other studies have observed that neither transactional nor transformational leadership directly affect the OCB (Dai, Dai, Chen, & Wu, 2013).…”
Section: Transactional Leadership Transformational Leadership and Ormentioning
confidence: 95%
See 3 more Smart Citations